2018
DOI: 10.30848/pjb2019-1(43)
|View full text |Cite
|
Sign up to set email alerts
|

Role of PGPR in the reclamation and revegetation of saline land

Abstract: A field experiment was conducted to investigate the effect of PGPR inoculation on growth and yield of maize as well as on reclamation of saline sodic soil of Soil Salinity Research Institute Pindi Bhattian Pakistan, during 2015-16. Seed of maize genotype "Islamabad Gold" were soaked (2-3 h) prior to sowing in the broth culture of 4 bacterial strains i.e. Pseudomonas putida (accession no. KX580766), Pseudomonas fluorescens (accession no. KX644132), Exiguobacterium aurantiacum (accession no. KX580769), Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…In both experimental fields, the application of PGPB consortium increased total organic carbon, organic matter and available P and allowed to keep higher concentrations of the other nutrients. These findings have been already reported by other authors [14,15] and can be ascribed to the PGPB capability of nutrient mobilization and to atmospheric nitrogen fixation [2]. The ecological indexes calculated on NGS results showed that seed bacterization was able to positively influence soil microbial community composition of both varieties, by increasing microbial biodiversity.…”
Section: Resultssupporting
confidence: 86%
“…In both experimental fields, the application of PGPB consortium increased total organic carbon, organic matter and available P and allowed to keep higher concentrations of the other nutrients. These findings have been already reported by other authors [14,15] and can be ascribed to the PGPB capability of nutrient mobilization and to atmospheric nitrogen fixation [2]. The ecological indexes calculated on NGS results showed that seed bacterization was able to positively influence soil microbial community composition of both varieties, by increasing microbial biodiversity.…”
Section: Resultssupporting
confidence: 86%
“…However, only limited data is available regarding the PGP activities showed by E . aurantiacum ( Ullah and Bano, 2019 ). Strahsburger et al (2018) reported the draft genome of E .…”
Section: Discussionmentioning
confidence: 99%
“…aurantiacum substantially increased the growth and yield of wheat crop grown under saline conditions. It may be due to the fact that these PGPR were able to metabolize ACC deaminase, solubilize insoluble phosphate minerals and produce a significant quantity of IAA ( Ullah and Bano, 2019 ). However, in our study, B. pumilus (T 3 ) and E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations